Comparative Analysis of Diesel Generators With Other Alternatives (Solar Plant, Thermal Power Plant) - Delphi, Ali; Saif, Yaqoob; Abdulrazzaq, Layth (Physical Sciences, Life Science and Engineering, 2025)
This paper tries to find best option for generating electricity during shortage by main grid in Al-kut city so analysis has been made for the three choices the diesel generator (which currently used by the city), solar power plants, and thermal power plant the analysis involve the total cost, how much carbon dioxide emitted and the water consumption by each system during the operation time. The study aims to find what is the best system for ten years, so estimation has been done to find what will be the population size of Al-kut city in 2033.inresult has been included keep adopted diesel generators for avoid issue of main grid shortage supply is cost city a lot by fuel consumption and cost of operation, furthermore there is significant amount of co2 emitted during the ten years. On another hand the most sustainable option the city should employ is the solar plant which has economical total cost compared to the thermal plant which cost high by requiring fuel to run, the solar has lowest water consumption and almost zero co2 emission in addition the solar system is reliable than others.